Hubungan Minat Belajar dan Keterampilan Proses Sains Siswa Sekolah Dasar - Amalina, Gita Febby; Suryani, Ela (Paedagogie, 2026)
This study aims to determine the relationship between learning interest and science process skills of fourth-grade elementary school students. The study uses a quantitative approach with a correlational design involving 89 fourth-grade students in the Melati Cluster, Sumowono District. Learning interest data were collected using a Guttman scale questionnaire, while science process skills were measured through objective tests that had met validity and reliability tests. Data analysis techniques used descriptive statistics and Pearson Product Moment correlation tests after the data met the prerequisites of normality and linearity. The results showed that students' learning interest was in the very high category, while their science process skills were in the moderate category. The correlation test results showed a positive and significant relationship between learning interest and science process skills among fourth-grade students. These findings indicate that the higher the students' learning interest, the better their science process skills. This study implies that developing students' learning interest needs to be a primary concern in science education in elementary schools.